Effect of nutrient management on growth and yield of sesame (Sesamum indicum L.): EFFECT OF NUTRIENT MANAGEMENT ON GROWTH AND YIELD OF SESAME - M R DESHMUKH; ALOK JYOTISHI; A R G RANGANATHA (Journal of Oilseeds Research, 2014)
Field experiments were conducted on sesame in vertisols of Jabalpur, Madhya Pradesh during kharif seasons of 2009-10 and 2010-11 to determine its efficient nutrient management. Results revealed that application of 100% recommended dose of fertilizers (RDF) as 60 kg N + 40 kg P2O5 + 30 kg K2O/ha superimposed with sprayings of 2% Diammonium phosphate (DAP) twice at flowering and capsule formation stages was the best nutrient management for sesame resulting in high seed yields and monetary advantages, which was comparable to 100% RDF + sprayings of 2% urea twice at flowering and capsule formation stages as well as 100% RDF + spraying of 2% DAP once at flowering stage. This nutrient management proved to be more remunerative also.